ANALISA ORGANOLEPTIK DAN ENUMERASI CEMARAN BAKTERI PADA TELUR ASIN DENGAN PERLAKUAN PERENDAMAN DAUN SIRIH ( Piper betle L.) - Setyawan, Zuhdi; Pratama, Muh Doddy; Purbawati, Purbawati; Jati Palupi, Pratiwi; Prasetia, Retno (Universitas Nahdlatul Ulama Kalimantan Timur, 2024)
Eggs easily experience a decrease in quality caused by the evaporation of water and CO₂. This study aimed to study the effect of soaking betel leaves (Piper betel L.) in improving the quality of salt eggs, analyzed by the number of bacteria, and the quality of salted eggs. The research was conducted by a completely randomized design (RAL), the data were analyzed using the ANOVA test and BNJ as further test with a significance level of 5%. The sample of this research was 120 duck eggs divided into 4 groups that were with no soaking (AB1), and with soaking of betel solution at concentrations 20% (AB2), 30% (AB3), and AB4 (40% solution)) with 3 replicates for the organoleptic test and 2 for the bacterial contamination test. The best result of the organoleptic test was at a concentration immersion of 40% while the total bacteria in salted eggs soaking 30% obtained a value of 35x104 cfu/gr. Thus, the soaking of salted eggs at 40% was the most favored by panelists. The results of salted eggs treated with betel leaf solution at a concentration of 30% provided the least amount of bacterial contamination compared to others.